2021
DOI: 10.18371/fcaptp.v1i32.200522
|View full text |Cite
|
Sign up to set email alerts
|

Rule of Law and Economic Growth

Abstract: Using data from 41 countries for the 2013-2018 period, the dependence of GDP growth on the rule of law index that is calculated by the non-governmental organization World Justice Project has been estimated. Compared to other specialized indicators for assessing compliance with the rule of law, such as the World Governance Indicator, the International Country Risk Guide, or the Index of Judicial Independence, the WJP differs more fully into actual legal practice (not only the quality of legislation) by combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…Consistent with the findings of Shevchuk et al. (2020), this study observed positive effect of RL on economic growth.…”
Section: Empirical Results and Their Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with the findings of Shevchuk et al. (2020), this study observed positive effect of RL on economic growth.…”
Section: Empirical Results and Their Discussionsupporting
confidence: 91%
“…Consistent with the findings of Shevchuk et al (2020), this study observed positive effect of RL on economic growth. By giving people access to justice, guaranteeing due process and enabling remedies for rights violations, the RL promotes development by enhancing the voices of people and communities.…”
Section: Ajebsupporting
confidence: 91%
See 1 more Smart Citation